From policy to practice : the anthropology of condom use - Da Cruz, Claudia Cristina B R (Social Anthropology, 2023)
AIDS and HIV infection rates are climbing amongst young people in South Africa in the last decades, despite various intervention initiatives by National Government and Non-governmental organisations alike. This dissertation explores the knowledge, beliefs and attitudes towards condom use amongst young people in the Northern and Western Cape in an attempt at understanding some of the cultural factors that inform sexual behaviour. It aims to explore issues of knowledge and the institutional culture of the clinic that invariably impacts on the sexual practices of individuals being targeted by such policies. It also hoped to investigate and offer an insight into the persistence of high-risk sexual practices amongst young people despite their having access to barrier contraceptive methods, condoms. I illustrate my argument through the analysis of data acquired in fieldwork earned out in two government clinics through the use of multi-faceted methodologies. The research applied anthropological, qualitative and quantitative research methods including focus group discussions, participant observation and in-depth follow-up interviews through the use of a detailed questionnaire. The questionnaire lent itself to the collection of both quantitative and qualitative data, through its structured, semi structured and open-ended questions. The overall findings of this research show that firstly, young men chose to use condoms selectively and the type of relationship they find themselves in appears to impact directly on this selection process. Secondly, younger women in this study seem to use condoms more regularly than their older counterparts and there appears to be a general dis-use of condoms within 'stable' relationships. Thirdly, lack of empowerment amongst women has a direct impact on their ability to negotiate condom use within sexual relationships. This research has also shown that there are some real and perceived challenges and constraints facing intervention strategies in terms of condom procurement and overall access to reproductive health services. Lastly, the overall aims of this research attempts to highlight the important contributions applied anthropology can make to the understanding of the various beliefs, practices and culture of condom use so as to better inform existing policies in the field of AIDS and HIV.